DIVERSIDADE GENÉTICA E MORFOMÉTRICA DE Hoplias malabaricus (BLOCH, 1794) EM DRENAGENS DO ESTADO DO MARANHÃO - SOUZA, Camila Penha Abreu (2014)
Hoplias malabaricus is a caraciforme of wide distribution, popularly known like traíra, that occurs in all the great Brazilian watersheds,presenting a small morphological differentiation and great karyotype variety.Since the population of H. malabaricus in the state of Maranhão presents only a cytotype recognized for this region, the present study examined its diversity in the Maranhão hydrographic region using geometric morphometry techniques and molecular diversity, associating the patterns found with geomorphological data and paleohydrologic processes of the drainage involved. Samples of H. malabaricus were collected from the rivers Turiaçu, Pindaré Mearim, Itapecuru, Munim, Gurupi, Parnaíba and Tocantins. The morphometric data, obtained from 15 anatomical landmarks, were submitted to a Canonical Variable Analysis (CVA). For molecular analysis two markers were used, the control region (D-Loop) of the mitochondrial DNA and the S7 intron 1 nuclear gene. Morphometric analyzes indicated significant variations among populations. In general, the differences were related in the variation of the head region and shortening / elongation of the caudal region. Molecular analysis Indicated the presence of eight Haplogroups (A-H) for D-loop and three groups (Group I, Group II and Group III) for the nuclear gene S7 íntron 1. The results found suggest high genetic diversity in specimens of H. malabaricus in the basins along the north-northeast region of Brazil with discreet morphometric variation. Such diversity seems to be related to the main events of diversification of freshwater fish, evidencing a possible speciation event cryptic of H. malabaricus in the studied region.